DESIGNING SEQUENTIAL SPEAKING SYLLABI FOR HIGHER EDUCATION THROUGH AI-ENHANCED PBL - Ikawati, Listiana; Nashruddin, Wakhid (IAIN Syekh Nurjati Cirebon, 2025)
Indonesia's persistently low English Proficiency Index (EPI) is caused by limited literacy and traditional pedagogies, resulting in weak speaking competency. This study aimed to create sequential speaking course syllabi incorporating Artificial Intelligence (AI) into Project-Based Learning (PBL) to enable enhanced speaking skills in higher education. Employing a Research and Development (R&D) design streamlined from Borg and Gall into three phases consisting of preliminary study, development, and validation. The study collected data through focus group discussions, interview, document analysis, and expert verification. Three syllabi were constructed on Speaking for Daily Purposes, Speaking at Workplace, and Speaking for Academic Purposes that were aligned with CEFR levels B1, B2, and C1. Validation employed two experts: an AI expert and a PBL-speaking expert. Scores indicate high feasibility, 90, 91, and 89 in AI expert scores, and 79.7 in PBL-speaking expert scores across syllabi, which are in the